2017
DOI: 10.3406/paleo.2017.5765
|View full text |Cite
|
Sign up to set email alerts
|

Prehistory of human tuberculosis: Earliest evidence from the onset of animal husbandry in the Near East

Abstract: La tuberculose a été considérée, pendant longtemps, comme une zoonose transmise à l'homme par des bovins, notamment lors du processus de domestication de l'aurochs au Néolithique. Des travaux de phylogénie moléculaire récents ont remis en question ce dogme, montrant que le complexe Mycobacterium tuberculosis (MTBC) a existé comme pathogène humain depuis environ trois millions d'années. Cependant, des études récentes basées sur deux horloges moléculaires différentes ont proposé que la tuberculose humaine date d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…A final form of data which should be taken into account when considering Mtb emergence scenarios comes from the fields of paleomicrobiology and ancient DNA 106 – 108 . These studies, which amplify Mtb sequence motifs, have produced evidence consistent with the presence of the pathogen in samples from Neolithic Israel 109 , 110 , Syria 111 , 112 , Germany 113 , Hungary 114 116 , Egypt 117 and Britain 118 , dating up to an estimated 10.8Kya. Multiple studies have also detected the TbD1 deletion 110 , 113 , 117 , 118 , implying that evolutionarily modern lineages were present at these timepoints.…”
Section: Discussionmentioning
confidence: 84%
“…A final form of data which should be taken into account when considering Mtb emergence scenarios comes from the fields of paleomicrobiology and ancient DNA 106 – 108 . These studies, which amplify Mtb sequence motifs, have produced evidence consistent with the presence of the pathogen in samples from Neolithic Israel 109 , 110 , Syria 111 , 112 , Germany 113 , Hungary 114 116 , Egypt 117 and Britain 118 , dating up to an estimated 10.8Kya. Multiple studies have also detected the TbD1 deletion 110 , 113 , 117 , 118 , implying that evolutionarily modern lineages were present at these timepoints.…”
Section: Discussionmentioning
confidence: 84%
“…Molecular studies confirmed TB in ancient human remains from necropoles in Ancient Egypt [78], Asia [79,80], America [81][82][83][84], and Europe [77,[85][86][87][88][89][90][91][92][93][94][95][96][97][98][99][100]. These authors reported aDNA extracted and analyzed and positively tested for MBTC, both from vertebral lesions and highly associated lesions.…”
Section: Established and Emerging Techniques For Molecular Studiesmentioning
confidence: 96%
“…Subsequently, rectangular houses in the Rössen culture (4,600-4,300 BC) were developed into trapezoidal forms, probably due to some cultural connection with the inflow of new inhabitants The Rössen houses were much longer than in Linearbanderkeramik culture; the longest known of this culture, a building from Inden, Germany, was ca. 52 m long with the central part of 31 m (Bakels, 2009). This house had a kind of antechamber separated by a wall from the central part where timber posts supporting the roof were grouped into triple rows; its rear part was the narrowest with a roof supported by single posts and most probably served sleeping purposes.…”
Section: Need For Shelter and Airmentioning
confidence: 99%